B8 Ablation of p62 modulates levels of soluble and aggregated mutant huntingtin and delays end-stage disease in R6/2 mice. (13th September 2016) - Sathasivam, Kirupa; Paredes, Casandra Gomez; Kuhlbrodt, Kirsten; Thiede, Christina; Reindl, Wolfgang; Smith, Edward J; Benjamin, Agnesska C; Franklin, Sophie A; Whitehouse, Caroline A; Herrmann, Frank; Tillack, Karsten; Macdonald, Douglas; et al.
Abstract : Background: N-terminal fragments of the mutant huntingtin (HTT) protein aggregate into oligomeric and fibrillary structures that can be detected as polyubiquitylated inclusion bodies in tissue sections from HD patients and mouse models of HD. Misfolded and aggregated proteins are degraded through two main intracellular protein clearance systems, the ubiquitin–proteasome system (UPS) and the autophagy–lysosome pathway. p62 is an adapter protein that regulates the proteolysis of ubiquitylated proteins via selective autophagy. In both the R6/2 and Hdh Q150 knock-in mice, p62 relocates to the nucleus with disease progression where it forms high molecular weight structures and co-localises with HTT inclusions. Aims: To investigate the effect of the constitutive ablation of the p62 gene on HD-related phenotypes in the R6/2 mouse model of HD. Methods: R6/2 mice that were heterozygous for p62 knock-out (p62Het) to p62Het females to generate WT, p62Het, p62 homozygous knock-out (p62Hom); R6/2, R6/2::p62Het and R6/2::p62Hom progeny. The effect of p62 ablation was assessed by multiple biochemical, immunohistochemical and behavioural approaches. Results: We have been able to demonstrate that the levels of soluble and aggregated HTT are decreased in multiple brain regions of R6/2::p62Hom mice, as compared to their R6/2 littermates and that this effect becomes more pronounced with disease progression. Ablation of p62 in R6/2 mice did not modify the failure of R6/2 mice to gain body weight, or impairments in rotarod performance, grip strength or activity but did delay end-stage disease as previously reported (Kurosawa et al ., 2014). Similarly, ablation of p62 did not improve dysregulated transcriptional profiles. Conclusion: Unravelling the mechanism by which the manipulation of p62 modulates soluble and aggregated HTT levels will lead to a greater understanding of the aggregation and clearance of mutant HTT. Funding: CHDI Foundation